Impact of Different Types of Lymphadenectomy Combined With Different Extents of Tumor Resection on Survival Outcomes of Stage I Non-small-cell Lung Cancer: A Large-Cohort Real-World Study - Wang, Weidong; Chen, Dongni; Xi, Kexing; Chen, Yongqiang; Zhang, Xuewen; Wen, Yinsheng; Huang, Zirui; Yu, Xiangyang; Wang, Gongming; Zhang, Rusi; Zhang, Lanjun (Frontiers in Oncology, 2019)
Background: To investigate the prognostic impact of different types of lymphadenectomy with different extents of tumor resection on the outcomes of stage I non-small cell lung cancer (NSCLC). Methods: Patients were classified into lobectomy and sublobectomy groups, and then each group was subdivided according to the types of lymphadenectomy. The end points of the study were overall survival (OS) and disease-free survival (DFS). Propensity score-matched (PSM) comparative analysis and univariate and multivariate Cox regression analyses were performed. Result: Totally, 1336 patients were included in the current study. Lobectomy was associated with better OS and DFS. In the lobectomy group, lobectomy with bilateral mediastinal lymphadenectomy (BML) was associated with better OS than lobectomy with systematic nodal dissection (SND) or lobe-specific systematic node dissection (L-SND). Lobectomy with SND or L-SND was associated with better OS than lobectomy with systematic nodal sampling (SNS) or selected lymph node biopsy (SLNB). Additionally, lobectomy with BML or SND was associated with better DFS than lobectomy with L-SND or SNS or SLNB. After PSM, lobectomy with SND resulted in more favorable OS and DFS compared with lobectomy with SNS or SLNB. There was no survival difference between different types of lymphadenectomy for patients who underwent sublobectomy. A multivariable analysis revealed independent associations of lobectomy with BML or SND with better OS and DFS compared with lobectomy with SNS or SLNB. Conclusion: This study reveals an association of lobectomy with more systematic and complete lymph node dissection, such as BML or SND, with better prognosis in stage I NSCLC patients.